2019
DOI: 10.1016/s0140-6736(18)32592-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological predictors of response to standardised paediatric colitis therapy (PROTECT): a multicentre inception cohort study

Abstract: Background-The lack of evidence-based outcomes data leads to uncertainty in developing treatment regimens in children newly diagnosed with Ulcerative Colitis (UC). We hypothesized that pre-treatment clinical, transcriptomic, and microbial factors predict disease course. Methods-We performed an inception cohort study of 428 paediatric UC patients receiving standardised mesalazine or corticosteroids (CS), with pre-established criteria for escalation to thiopurines or anti-TNFα. RNA sequencing (n=206) defined pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
160
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(172 citation statements)
references
References 35 publications
3
160
2
1
Order By: Relevance
“…These findings reflect the complexity of achieving remission in youth with UC, as a number of factors have been shown to contribute to future remission status, including disease activity early in the disease course . Specifically, in the PROTECT main study, lower baseline severity, higher baseline haemoglobin and initial response to therapy (ie clinical remission at week 4) were all significantly associated with steroid‐free remission at week 52 . In adults with UC, electronically monitored adherence to mesalazine was the distinguishing factor between disease relapse and remission.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…These findings reflect the complexity of achieving remission in youth with UC, as a number of factors have been shown to contribute to future remission status, including disease activity early in the disease course . Specifically, in the PROTECT main study, lower baseline severity, higher baseline haemoglobin and initial response to therapy (ie clinical remission at week 4) were all significantly associated with steroid‐free remission at week 52 . In adults with UC, electronically monitored adherence to mesalazine was the distinguishing factor between disease relapse and remission.…”
Section: Discussionmentioning
confidence: 93%
“…Covariates were age, sex and baseline disease characteristics, including PUCAI, haemoglobin, Vitamin D and lower rectal biopsy eosinophil count. Vitamin D level at baseline and lower rectal biopsy eosinophil count were included as additional covariates in the model predicting need for rescue as findings from the PROTECT trial demonstrated individuals with pre‐treatment Vitamin D levels of 25(OH)D <20 ng/mL and pre‐treatment rectal eosinophils <32/hpf were more likely to escalate to anti‐TNFα . Of note, the current study modelled the association between longitudinal adherence and any treatment escalation, therefore our sample was not identical to the previous study predicting only escalation to anti‐TNFα.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations